Evaluation of two approaches to organizational change for small and medium sized businesses - Mackness, John (Sunway University College, 2008)
This study examines two different approaches to organizational change: one focusing on solving specific problems and the other focusing on changing the organizational culture. The opportunity for the author to evaluate the different approaches came about because a government-financed development agency working to develop a specific region of the UK, wanted to know how best to allocate its scarce resources to initiate change to improve productivity in assembly and manufacturing industries. Both approaches had been used recently but the agency wanted an objective assessment of their strengths and weaknesses before deciding to promote one or the other. The evaluation showed that both models could produce good results. However, the scope, scale and impact of the problem solving approach was much less than the culture change approach. This was primarily due to the changes in values and commitment of staff and their willingness to initiate change projects and be part of the change process.